Intergenerational continuity of protective parenting practices in Dhaka, Bangladesh - Jasmine, Umme Habiba; Nkala-Dlamini, Busisiwe (Public Library of Science, 2025)
Intergenerational transmission of parenting practices is a new dimension of research in Bangladesh. This study used a social cognitive theory framework along with a theory of urbanization and a theory of modernization to examine the continuity of protective parenting practices across two generations. A cross-sectional hermeneutic phenomenological study design was followed from a social constructivist paradigm. Eleven maternal grandmothers (G1) and 11 mothers (G2) were purposively selected from Mirpur, Dhaka, Bangladesh. Data were collected through semi-structured, in-depth interviews. The mothers learned protective parenting practices from the grandmother generation through direct instruction, experience, observation, and modeling within an interaction of various social elements. Protective parenting practices were found to be essential and persisted with some modifications despite modernization. Based on the findings, a process model of intergenerational continuity of parenting practices has been offered, which depicts intergenerational learning within a transitional social context.
Keywords: Mothers; Parenting behaviour; Human learning; Urbanisation; Social theory; Human families; Culture; N/A